Air‐Processed Organic Photovoltaics for Outdoor and Indoor Use Based upon a Tin Oxide‐Perylene Diimide Electron Transporting Bilayer. Issue 3 (8th December 2021) - Munir, Rahim; Cieplechowicz, Edward; Lamarche, Renaud Miclette; Chernikov, Roman; Trudel, Simon; Welch, Gregory C.
Abstract: Efficient organic photovoltaics (OPV) based on SnO2 | perylene diimide (PDI) bilayer as an electron transport layer (ETL) is fabricated and tested in an ambient environment. The PTQ10:Y6 photoactive system is used as the primary bulk‐heterojunction. Without any surface treatment, the power conversion efficiency (PCE) of SnO2 ‐based OPV devices is 1.5%. Treating the SnO2 nano‐particles with UV‐ozone and then applying a layer of N‐annulated PDI with a functional NH bond (PDIN‐H) on top increase device PCEs to 9.2%. For indoor applications, the OPV device PCE rises from 8.1% to 12.3% when PDIN‐H is employed on SnO2 and tested under low light conditions, without the need for light soaking. The SnO2 | PDIN‐H ETL bilayer is slot‐die coated and corresponding OPV devices have a PCE of 7.9%, demonstrating utility for OPV scale‐up. The hybrid ETL is tested with other photoactive systems employing Y6, Y7, and IDIC as acceptors, as well as PM6 donor, and all these cases yield OPV devices with improved PCE when compared to OPV devices with SnO2 ‐only ETLs. These results show the successful implementation of SnO2 | PDIN‐H as an ETL for OPV. Abstract : Hybrid SnO2 /PDIN‐H bilayer as an electron transport layer for organic solar cells is demonstrated. It improves device performance for outdoor and indoor applications, increases devices stability, can be scaled via slot‐die coating, and is applicable for several different photoactive layer combinations.